Increased Abundance of Lactobacillales in the Colon of Beta-Adrenergic Receptor Knock Out Mouse Is Associated With Increased Gut Bacterial Production of Short Chain Fatty Acids and Reduced IL17 Expression in Circulating CD4+ Immune Cells - Bartley, Akeem; Yang, Tao; Arocha, Rebeca; Malphurs, Wendi L.; Larkin, Riley; Magee, Kacy L.; Vickroy, Thomas W.; Zubcevic, Jasenka (Frontiers in Physiology, 2018)
Emerging evidence suggests an associative link between gut dysbiosis, the autonomic nervous system (ANS) and the immune system (IS) in pathophysiology of neurogenic hypertension (HTN). However, the close interplay between these three systems presents us with difficulties in deciphering the cause-effect relationship in disease. The present study utilized beta 1 and 2 adrenergic receptor knock out (AdrB1tm1BkkAdrB2tm1Bkk/J KO) mice to isolate the effects of reduced overall sympathetic drive on gut microbiota and systemic IS. We observed the following: (i) Diminished beta adrenergic signaling mainly reflects in shifts in the Firmicutes phyla, with a significant increase in abundance of largely beneficial Bacilli Lactobacillales in the KO mice; (ii) This was associated with increased colonic production of beneficial short chain fatty acids (SCFAs) butyrate, acetate and propionate, confirming functional microbiota shifts in the KO mice; (iii) Dampened systemic immune responses in the KO mice reflected in reduction on circulating CD4+.IL17+ T cells and increase in young neutrophils, both previously associated with shifts in the gut microbiota. Taken together, these observations demonstrate that reduction in the sympathetic nervous system may lead to beneficial shifts in the gut microbiota and lower specific immune response. This suggests that dietary intervention, through probiotics, may be a viable option in correcting gut dysbiosis and treatment of symptoms of neurogenic HTN.